Genomic characteristics of Mycobacterium tuberculosis isolates of cutaneous tuberculosis - Mei, You-Ming; Zhang, Wen-Yue; Sun, Ji-Ya; Jiang, Hai-Qin; Shi, Ying; Xiong, Jing-Shu; Wang, Le; Chen, Yan-Qing; Long, Si-Yu; Pan, Chun; Luo, Tao; Wang, Hong-Sheng (Frontiers in Microbiology, 2023)
Objectives Cutaneous tuberculosis with various manifestations can be divided into several clinical types according to the host's immune status and infective route. However, the etiological factors of this disease remain unclear. The objective of this study is to investigate the pathogens associated with the occurrence and different types of cutaneous tuberculosis. Methods 58 Mycobacterium tuberculosis strains isolated from cutaneous tuberculosis over the last 20 years were sequenced and analyzed for genomic characteristics including lineage distribution, drug-resistance mutations, and mutations potentially associated with different sites of infection. Results The M. tuberculosis strains from four major types of cutaneous tuberculosis and pulmonary tuberculosis shared similar genotypes and genomic composition. The strains isolated from cutaneous tuberculosis had a lower rate of drug resistance. Phylogenic analysis showed cutaneous tuberculosis and pulmonary tuberculosis isolates scattered on the three. Several SNPs in metabolism related genes exhibited a strong correlation with different infection sites. Conclusions The different infection sites of TB may barely be affected by large genomic changes in M. tuberculosis isolates, but the significant difference in SNPs of drug resistance gene and metabolism-related genes still deserves more attention.